Sleep disorders and sports-related travel and its effects on athletic performance - Boostani, M. H.; Boostani, M. A. (European Journal of Experimental Biology, 2014)
Sleep can be a common behavior in all animal species studied-ranging from insects to mammals the existence of which has been demonstrated be considered. Sleep is one of the most striking human behaviors and encompasses approximately one- third of human life. It is thought that clutter and disorder in sleep, in some cases merely a result of the automated systems of the body until signs and symptoms of disease as of the pain. However, the system is equipped with mammal organisms whose main role is to maintain balance in the body. Finally, it should be stated, insomnia can effect certain hormones, and they can lead to adverse effects. In addition, the influence of their effect we response time that can get rid of the undesirable side effects of these factors makes it unpredictable. So, according to what was said during the sleep disruptions in travel, sports, could possibly be considered as a factor effecting the endocrine system. It also seems to be sleeping on people's responses influence the severity of this effect is a function of the duration of the trip and is disrupted in its wake.